Acylation of Oleanolic Acid Oximes Effectively Improves Cytotoxic Activity in In Vitro Studies - Barbara Bednarczyk-Cwynar; Piotr Ruszkowski (MDPI AG, 2024)
(1) Background: The aim of the presented work was to obtain a set of oleanolic acid derivatives with a high level of anticancer activity and a low level of toxicity by applying an economic method. Three types of oleanolic acid derivatives were obtained: (i) derivatives of methyl oleanonate oxime, (ii) derivatives of methyl oleanonate oxime with an additional 11-oxo function, and (iii) derivatives of morpholide of oleanonic acid oxime. (2) Methods: The above oximes were acylated with aliphatic or aromatic carboxylic acid. The newly obtained compounds were subjected to ADMETox analysis and were also tested for cytotoxicity activity on the HeLa, KB, MCF-7, A-549, and HDF cell lines with the MTT assay. (3) Results: Among the tested acylated oximes of oleanolic acid, some derivatives, particularly those with two nitro groups attached to the aromatic ring, proved to be the most potent cytotoxic agents. These triterpene derivatives significantly inhibited the growth of the HeLa, KB, MCF-7, and A-549 cancer cell lines in micromolar concentrations. (4) Conclusions: The introduction of different moieties, particularly the 3,5-dinitro group, resulted in the synthesis of highly potent cytotoxic agents with favorable SI and ADMETox parameters.